Finding purpose in a godless world why we care even if the universe doesn't - Lewis, Ralph (Prometheus Books, 2018)
"A psychiatrist presents a compelling argument for how human purpose and caring emerged in a spontaneous and unguided universe. Drawing on years of wide-ranging, intensive clinical experience, and his own family experience with cancer, the author helps the reader to understand how people cope with random adversity without recourse to supernatural belief. In fact, as he explains, coming to terms with randomness, while initially frightening, can be liberating and empowering. Realizing that the universe is fundamentally random is not usually the cause of nihilism, apathy, or feelings of pointlessness about life. Written for those seeking a scientifically sound yet humanistic worldview, the book examines science's inroads into the big questions claimed by religion and philosophy. Dr. Lewis shows how our mistaken intuitions about purpose are entangled with assumptions that life events happen for an intended reason and that the universe has inherent purpose. Integrating disparate scientific fields, he shows how not only the universe, life, and consciousness could have emerged and evolved spontaneously and unguided - so too could purpose, morality, and meaning. There is persuasive evidence that these qualities evolved naturally and unmysteriously in humans, as conscious, goal-directed social animals. While acknowledging the social and psychological value of progressive forms of religion, the author respectfully deconstructs even the most sophisticated theistic arguments for a purposeful universe. Instead, he offers an evidence-based, realistic yet optimistic, compassionate worldview"...
Includes bibliographical references and index
Keywords: RELIGION / Atheism / bisacsh; RELIGION / Psychology of Religion / bisacsh; Meaning (Psychology); Psychology, Religious; RELIGION / Atheism; RELIGION / Psychology of Religion; Sinn; Nihilismus